One artist, one material : fifty-five makers on their medium - Castle, Elena, ....- (Amsterdam : Frame, 2018)
In an age of digital predominance, One Artist, One Material celebrates the limitations and possibilities of physical materials, by means of interviews with 50 world-renowned artists about their material of choice. Over the course of their careers, many artists develop a preference for a particular material, allowing them to become intimately familiar with its physical possibilities and limitations. The artists who share their valuable experiences in this book include Clint Baclawski, James Bridle, Berline de Bruyckere, Jordan Eagles, Martin Huberman, Yusuke Kamata, Mark Khaisman, Jonas Lund, Jorge Otero-Pailos, John Sabraw, Philip Stearns, Hanayuishi Takaya, and Rebecca Ward. One Artist, One Material is a collection of articles that appeared in the eponymous section in Frame magazine. Published since 2008, 'One Artist, One Material' is one of the longest-running and most successful sections of the magazine. Revisiting each of these interviews for compilation into this new book, One Artist, One Material includes new material and further insights. The book also features the most important projects with which these established creatives made their name.
Keywords: Kunst ; materialen